2019
DOI: 10.1590/s0102-8650201900209
|View full text |Cite
|
Sign up to set email alerts
|

Milk fat globule-epidermal growth factor 8 (MFG-E8) attenuates sepsis-induced acute kidney injury by inhibiting NF-κB signaling pathway

Abstract: Purpose To explore the effect of milk fat globule-epidermal growth factor 8 (MFG-E8) on sepsis-induced acute kidney injury (SAKI). Methods Male C57BL/6 mice were randomized to control, sham, CLP, CLP+PBS, and CLP+rmMFG-E8 groups. SAKI was induced by cecal ligation and puncture (CLP). Recombinant mouse MFG-E8 (rmMFG-E8) (20 μg/kg) or PBS (vehicle) was administered intraperitoneally. Blood, urine and renal tissue were collected at 24 h after CLP. Blood samples were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…However, whether the anti-inflammatory effect of MFG-E8 and the promotion of macrophage phagocytosis of apoptotic cells are related to the regulation of ER function remains unknown. Several studies have shown that MFG-E8 can directly regulate the NF-κB pathway (Zhao et al, 2019;Gong et al, 2020;Lu et al, 2021). In this study, we also found that MFG-E8 downregulated the NF-κB pathway.…”
Section: Discussionsupporting
confidence: 78%
“…However, whether the anti-inflammatory effect of MFG-E8 and the promotion of macrophage phagocytosis of apoptotic cells are related to the regulation of ER function remains unknown. Several studies have shown that MFG-E8 can directly regulate the NF-κB pathway (Zhao et al, 2019;Gong et al, 2020;Lu et al, 2021). In this study, we also found that MFG-E8 downregulated the NF-κB pathway.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have found that inflammation enhances and AS aggravates in mice lacking MERTK and MFGE8 ( Ait-Oufella et al, 2007 ; Cai et al, 2017 ; Triantafyllou et al, 2018 ). Several studies have shown that MFGE8 is a novel anti-inflammatory factor in multisystem diseases, such as neonatal sepsis, hepatic steatosis, rheumatoid arthritis and kidney injury ( Albus et al, 2016 ; Hansen et al, 2017 ; Zhao et al, 2019 ; Zhang et al, 2021 ). Additionally, MFGE8 level decreases in the CHD group and is negatively associated with the severity of coronary artery stenosis and the risk of clinical events ( Dai et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…82 Exogenous MFG-E8 may play a renoprotective role by inhibiting the NF-κB pathway to relieve renal inflammation and fibrosis levels in mice with sepsis. 83 Moreover, extracellular vesicles containing MFG-E8 alleviated renal fibrosis by inhibiting the RhoA/ROCK pathways in a rat model of renal fibrosis. 84 Therefore, the anti-fibrotic effect shown in sheep milk here may be related to the high content of anti-fibrotic substances, such as EGF.…”
Section: Discussionmentioning
confidence: 97%